Comparison of the Castelli-II Index Between Normal Weight Obesity and Obese Medical Students - Fadhilah Adawiyyah Alimbran; Filda Vionita Irene de Lima; Vina Zakiah Latuconsina; Rachmawati Dwi Agustin; Rahmi R. Latief; Irwan (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Cardiovascular disease remains the leading cause of mortality in Indonesia, with obesity recognized as a major risk factor. Excess body weight not only contributes to obesity but also alters lipid metabolism, thereby accelerating atherosclerosis. Interestingly, not all individuals with metabolic risk exhibit excess weight. This condition, termed normal weight obesity (NWO), describes individuals with a normal BMI (18.5-24.9 kg/m2) but an elevated body fat percentage (men >25%, women >30%). One of the important predictors of cardiovascular risk is the Castelli-II Index, defined as the LDL/HDL ratio, which reflects the balance between atherogenic and protective lipoproteins. This study aimed to evaluate the Castelli-II Index as a predictor of cardiovascular disease in individuals with NWO and obesity among medical students at the Faculty of Medicine, Universitas Pattimura. Methods. An analytic observational design with a cross-sectional approach was employed. A total of 52 respondents were recruited, comprising 26 individuals with NWO and 26 with obesity. BMI and body fat composition were assessed using a bioelectrical impedance analyzer (BIA), while LDL and HDL levels were determined through direct enzymatic testing. Results. Bivariate analysis using the chi-square test demonstrated no statistically significant difference in the Castelli-II Index between the NWO and obesity groups (p = 0.235). Conclusion. In conclusion, despite differences in body composition, the Castelli-II Index did not significantly differ between students with NWO and those with obesity. Further studies with larger and more diverse samples are recommended to validate the role of the Castelli-II Index in predicting cardiovascular risk among young adults.